1998
DOI: 10.1002/(sici)1097-0142(19980501)82:9<1664::aid-cncr11>3.0.co;2-2
|View full text |Cite
|
Sign up to set email alerts
|

Primary staging and follow-up of high risk melanoma patients with whole-body18F-fluorodeoxyglucose positron emission tomography

Abstract: ported to be a sensitive method for detecting malignant melanoma metastases. METHODS. One hundred consecutive patients with high risk melanoma (tumor Gustav RESULTS.In Group A, the sensitivity of PET was 100% and the specificity was 94%, whereas CD did not identify any of the 9 lymph node metastases and demonstrated 2 Department of Nuclear Medicine, University of Frankfurt Medical Center, Frankfurt, Germany.a lower specificity (80%). In Group B, 121 lesions were detected, 111 by PET and 69 by conventional ima… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
100
1
4

Year Published

1999
1999
2013
2013

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 232 publications
(107 citation statements)
references
References 34 publications
1
100
1
4
Order By: Relevance
“…Results, however, depend on the experience of the examiner. The sensitivity of PET/MRT/CT is greater than that of abdominal sonography [626]. In a study by Kaufmann et …”
Section: Level Of Evidence 2bmentioning
confidence: 95%
See 1 more Smart Citation
“…Results, however, depend on the experience of the examiner. The sensitivity of PET/MRT/CT is greater than that of abdominal sonography [626]. In a study by Kaufmann et …”
Section: Level Of Evidence 2bmentioning
confidence: 95%
“…Systematic search of the literature de-novo: [116,614,625,626] Strength of consensus: 96 % I. Satzger, U. Leiter…”
Section: Level Of Evidence 2bmentioning
confidence: 99%
“…The fact that PET imaging is functional rather than structural limits its value in local tumour staging, but numerous studies have shown an effect in the identification of regional and distant disease (Rinne et al, 1998;Dwamena et al, 1999;Gould et al, 2001;Hellwig et al, 2001;Kalff et al, 2002), treatment decisions (MacManus et al, 2001;Spaepen et al, 2001;Blum et al, 2003;Heriot et al, 2004), radiotherapy planning (Haustermans et al, 2002;MacManus and Hicks, 2003;Leong et al, 2006) and in the prediction of response (Di Fabio et al, 2005;Duong et al, 2006).…”
mentioning
confidence: 99%
“…In patients with metastatic melanoma being considered for surgical intervention, PET scanning appears to be a particularly useful assessment tool [30]. PET has a higher sensitivity and speci®city than conventional imaging for detecting metastatic melanoma in all regions of body except the thorax [30,31]. In a study by Rinne and co-workers [31], PET was able to detect abdominal metastases in all known cases (25 of 25), compared with a 32% sensitivity (8 of 25) with conventional imaging.…”
Section: Discussionmentioning
confidence: 99%
“…PET has a higher sensitivity and speci®city than conventional imaging for detecting metastatic melanoma in all regions of body except the thorax [30,31]. In a study by Rinne and co-workers [31], PET was able to detect abdominal metastases in all known cases (25 of 25), compared with a 32% sensitivity (8 of 25) with conventional imaging. However, the sensitivity of PET is lower for tumours <1 cm, because of limitations of scanner resolution.…”
Section: Discussionmentioning
confidence: 99%